ECOWAS and Regional Integration in West Africa: From State to Emerging Private Authority - Oloruntoba, Samuel O. (History compass, 2016)
The Economic Community of West African States was established in 1975 due to the leadership initiative of Nigeria and Togo as well as the cooperation of other Heads of State and Governments in the subregion. It was established within the framework of the consciousness of the need to develop a regional platform for cooperation and development. Since inception various institutions have been established, treaties and protocols have been signed and deadlines have been set for realising the objective conditions for which the subregional body was set up. Integration and regionalism in Africa have seen some twists and turns depending on the prevailing socio-economic and ideological conditions both at the domestic and international environments. Various efforts have been made towards building regionalism in West Africa, especially within the context of neoliberal economic paradigm in which removal of barriers to market access and other factors of production is the main concern. Despite some successes, the effectiveness of the subregional body has been hampered through both domestic and external factors. News actors in form of private authority of indigenous multinational companies and other non-state actors are emerging which could facilitate integration in the sub-region in a more sublime and functional sense than the approach taken by political elites over the past 50 years. This paper discusses these new trends in integration within the theoretical prisms of networked political economy, private authority and regional identity. I also examine the institutional developments that have taken place since it was formed about 40 years ago.